ANALISIS DESKRIPTIF MULTIMEDIA INTERAKTIF FRENCH CITY, PLAY & LEARN FRENCH DALAM PEMBELAJARAN BAHASA PERANCIS - Rusydah, Qonitah Fatinah (2017)
This study aims to assess: (1) profile of interactive multimedia French City, Play & Learn French, (2) learning material presented in interactive multimedia French City, Play & Learn French is associated with the competency framework of European languages, namely CECRL (Cadre Européen Commun de référence pour les Langues) level A2, (3) the assessment of students to interactive multimedia French City, Play & Learn French. To achieve these objectives, the method used in this research is descriptive. In analyzing the data, researcher used a sheet format of multimedia assessement corresponding to the characteristics of interactive multimedia proposed by Warsita (2008, p.155), the calculation in response to a multimedia adaptation of Riduwan & Sunarto (20 13, P.23) and the analysis of learning materials level A2 refers to the theoretical level of DELF / DALF written by Chauvet et al (2008, p.15). Based on the results of the study, researcher found that: (1) interactive multimedia French City, Play & Learn French which has a rating 4.5 of 5 stars was officially created by the Institut Français République de Coree du Sud and Mathieu Baduel as a developer, (2) there are two language skills in interactive multimedia French City, Play & Learn French, they are listening and reading, not available material for speaking and writing skills, (3) the result of observation to determine the percentage of student assessment to interactive multimedia French City, Play & Learn French showed a good value is 80.83%, the highest value contained in a flexible and individual aspects. Based on these findings, researcher recommend the interactive multimedia French City, Play & Learn French as a complement, it can be used to train the ability of individual and can be used as a reference in creating a dialogue or conversation.;---Penelitian ini bertujuan untuk mengkaji: (1) profil multimedia interaktif French City, Play & Learn French, (2) materi pembelajaran yang disajikan dalam multimedia interaktif French City, Play & Learn French dikaitkan dengan kerangka kompetensi bahasa Eropa yaitu CECRL (Cadre Européen Commun de Référence pour les Langues) tingkat A2, (3) penilaian mahasiswa terhadap multimedia interaktif French City, Play & Learn French. Untuk mencapai tujuan tersebut, metode yang digunakan dalam penelitian ini adalah deskriptif. Dalam menganalisis data, peneliti menggunakan lembar format penilaian multimedia yang sesuai dengan karakteristik multimedia interaktif yang dikemukakan oleh Warsita (2008, p.155), perhitungan dalam penilaian multimedia yang diadaptasi dari Riduwan & Sunarto (2013, p.23) dan analisis materi pembelajaran tingkat A2 merujuk pada teori tingkatan DELF/DALF yang ditulis oleh Chauvet dkk (2008, p.15). Berdasarkan hasil penelitian, peneliti menemukan bahwa: (1) multimedia interaktif French City, Play & Learn French yang memiliki 4.5 dari 5 bintang ini resmi diciptakan oleh Institut Français République de Corée du Sud dan Mathieu Baduel sebagai pengembang, (2) terdapat dua keterampilan berbahasa dalam multimedia interaktif French City, Play & Learn French yaitu menyimak dan membaca, belum tersedia materi untuk keterampilan berbicara dan menulis, (3) hasil observasi untuk menentukan persentase penilaian mahasiswa terhadap multimedia interaktif French City, Play & Learn French menunjukkan nilai yang baik yaitu 80,83%, nilai tertinggi terdapat pada aspek fleksibel dan individual. Berdasarkan hasil penelitian tersebut, peneliti merekomendasikan multimedia interaktif French City, Play & Learn French untuk melatih kemampuan individu dan dapat dijadikan sebagai referensi dalam membuat dialog atau percakapan.